Health Education in Gestational Diabetes Mellitus and Quality of Life - Mani Mirfeizi; Zahra Mehdizadeh Tourzani; Mohammad Asghari Jafarabadi; Soheila Moghimi Hanjani; Mandana Hasanzad (Mashhad University of Medical Sciences, 2017)
Background & aim: Incidence rate of gestational diabetes mellitus (GDM) has been estimated to be 18.5%. GDM is associated with various challenges in terms of care and public health. The present study aimed to investigate the effects of health education and behavioral interventions on the quality of life in the patients diagnosed with gestational diabetes mellitus (GDM). Methods: This randomized controlled trial was conducted on 149 eligible participants, who were randomly assigned to the intervention and control group with the allocation ratio of 1:1. Participants were divided into four groups, including nutrition therapy with and without education and insulin therapy with and without education. Follow-up of the patients was performed during 12 weeks (January 2014-April 2015). The educational intervention consisted of various aspects, including diet, exercise, glycemic control, postpartum diabetes control and recommendations for delivery. Primary and secondary outcomes were the effects of the educational intervention on the metabolic control and quality of life, respectively. All the women completed the Iranian version of the Diabetes Quality of Life Brief Clinical Inventory (IDQL-BCI) prior to and after the educational intervention. Data analysis was performed using variance, covariance and Chi-square in SPSS version 15, at the significance level of 0.05. Results: No significant difference was observed between the four groups in terms of the quality of life score in the DQOL-BCL before the educational program. However, this score increased in all study groups, especially in the insulin therapy group (mean difference=16.43). Conclusion: According to the results, health education program could be effective in enhancing health-related quality of life in the women with GDM.